Gaza under British rule (1917-1948): Contradictory Promises and the Colonial Legacy in Palestine - Pedro FERREIRA; Mariana RODRIGUES (Bulletin of "Carol I" National Defense University)
This paper analyses the impact of British rule in Gaza between 1917 and 1948, highlighting the way in which the commitments made by Britain during the First World War influenced the political configuration of Palestine, specifically the territory of Gaza. The importance of this topic lies in the need to understand the historical origins of geopolitical tensions in the region, and is justified by the significant role of the British administration in articulating contradictory commitments to the Arabs and Jews, which triggered longlasting conflicts. The main objective is to evaluate the effects of these promises on Gaza and its population, particularly in the context of the British administration. The methodology adopted is historical-analytical, based on bibliographical research and the analysis of books and scientific articles. It concludes that British action has profoundly molded the socio-political reality of Gaza, contributing to territorial fragmentation, the political exclusion of Palestinian Arabs, and the aggravation of identity tensions. This analysis contributes to a critical understanding of the British legacy in Palestine.